Construction of 3D Creep Model of Landslide Slip-Surface Soil and Secondary Development Based on FLAC3D - Li Wang; Shimei Wang; Gao Li; Lin Wang (Advances in Civil Engineering)
Landslide deformations have predictable rheological properties, but, when using finite element analysis, only the elastoplastic constitutive equation of soil is considered. Soil creep properties are not considered, often rendering inaccurate results. In this paper, the three-dimensional state equation of the extended Burgers model is derived based on the creep test results of slip-surface soil and the Mohr–Coulomb elastoplastic model. This paper uses FLAC3D, a finite-element software platform, for secondary development and to verify the accuracy of the model and program. A strength reduction method that considers rheological properties is proposed. A numerical simulation of rheological properties is conducted on a landslide and compared with conventional viscoelastic constitutive results. It can be found that the landslide displacement calculation is significantly smaller when the rheological properties are not considered. The stability coefficient of the landslide calculated by the strength reduction method, considering the rheological properties, is smaller than the coefficient calculated without considering rheological properties.